Targeting the LRP5 Pathway Improves Bone Properties in a Mouse Model of Osteogenesis Imperfecta. (October 2014) - Jacobsen, Christina M; Barber, Lauren A; Ayturk, Ugur M; Roberts, Heather J; Deal, Lauren E; Schwartz, Marissa A; Weis, MaryAnn; Eyre, David; Zurakowski, David; Robling, Alexander G; Warman, Matthew L
ABSTRACT The cell surface receptor low‐density lipoprotein receptor‐related protein 5 (LRP5) is a key regulator of bone mass and bone strength. Heterozygous missense mutations in LRP5 cause autosomal dominant high bone mass (HBM) in humans by reducing binding to LRP5 by endogenous inhibitors, such as sclerostin (SOST). Mice heterozygous for a knockin allele (Lrp5p.A214V) that is orthologous to a human HBM‐causing mutation have increased bone mass and strength. Osteogenesis imperfecta (OI) is a skeletal fragility disorder predominantly caused by mutations that affect type I collagen. We tested whether the LRP5 pathway can be used to improve bone properties in animal models of OI. First, we mated Lrp5+/p.A214V mice to Col1a2+/p.G610C mice, which model human type IV OI. We found that Col1a2+/p.G610C;Lrp5+/p.A214V offspring had significantly increased bone mass and strength compared to Col1a2+/p.G610C;Lrp5+/+ littermates. The improved bone properties were not a result of altered mRNA expression of type I collagen or its chaperones, nor were they due to changes in mutant type I collagen secretion. Second, we treated Col1a2+/p.G610C mice with a monoclonal antibody that inhibits sclerostin activity (Scl‐Ab). We found that antibody‐treated mice had significantly increased bone mass and strength compared to vehicle‐treated littermates. These findings indicate increasing bone formation, even without altering bone collagen composition, may benefit patients with OI. © 2014 American Society for Bone and Mineral Research.